CORRESPONDENCE OF THEOPHYLACT OF OHRID: POLOG IN THE L8 AND L13A LETTERS (Annual of the Faculty of Philosophy in Skopje, 2011)
The Correspondence of Ohrid archbishop Theophylact is very precious source for Macedonian History from the end ofXth-beginning of Х1Ѓ Century. Two of his numerous Letters, denoted as L8 (dated in the Second Half / The End of the 1091) and LI3a, written in the First Half of the 1092, contain significant information about Polog''s administrative, socio-economic and church History at the end of Xfh Century.
Keywords: ARCHBISHOP THEOPHYLACT OF OHRID; POLOG; XI-XII CENTURY MACEDONIA